Role of state sector in developing countries (New Delhi, 1977)
An internatonal seminar on " The Role of the State Sector in the Developing Countries ", organised jointly by the Communist Party of India and the journal World Marxist Review was held in the capital of India, New Delhi, 10-12 December 1976. Taking part in the seminar were representatives of several fraternal parties represented on the journal, delegations of the communist and workers paties of Irag, Syria, Mongolia, GDR and Sril Lanka, and Soviet Scholars.
Keywords: Government business enterprises - developing countries